2023
DOI: 10.3389/fnins.2023.1061485
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of CD133 + Exosomes on liver function after stroke in type 2 diabetic mice

Abstract: Background and purposeNon-alcoholic fatty liver disease (NAFLD) is known to adversely affect stroke recovery. However, few studies investigate how stroke elicits liver dysfunction, particularly, how stroke in type 2 diabetes mellitus (T2DM) exacerbates progression of NAFLD. In this study, we test whether exosomes harvested from human umbilical cord blood (HUCBC) derived CD133 + cells (CD133 + Exo) improves neuro-cognitive outcome as well as reduces liver dysfunction in T2DM female mice.MethodsFemale, adult non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Importantly, the findings indicated a positive relevant between SAA levels and HOMA-IR, CRP, IL-6. SAA levels were also increased in the mouse model of diabetic stroke, which were the key factor for the progress of T2DM [ 37 ]. Our research clearly demonstrated that patients diagnosed T2DM who had IR displayed elevatory CRP and SAA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the findings indicated a positive relevant between SAA levels and HOMA-IR, CRP, IL-6. SAA levels were also increased in the mouse model of diabetic stroke, which were the key factor for the progress of T2DM [ 37 ]. Our research clearly demonstrated that patients diagnosed T2DM who had IR displayed elevatory CRP and SAA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Using a type 2 diabetes mellitus mouse model, Venkat et al demonstrated that HSC-derived exosomes could simultaneously reduce liver dysfunction and improve neurological and cognitive function. 249 Lastly, acute pancreatitis is an unpredictable and potentially lethal disease, the prognosis of which mainly depends on whether it develops into multiple organ dysfunction syndrome. 250 Chen et al revealed that exosomes from iPSC-derived MSCs could improve myocardial injury caused by severe acute pancreatitis through the Akt/Nrf2/HO-1 pathway.…”
Section: General Surgery and Sc-exo Therapymentioning
confidence: 99%
“…To investigate the role of EE in promoting neuroplasticity, we assessed the expression of DCX (a marker of neuroblasts and immature neurons) and Nestin (a neural stem cell marker) [14] and determined the infarct volume and neurobehavioral scores of rats with cerebral I/R injury [15]. We also focused on the development of axons and dendrites.…”
Section: Introductionmentioning
confidence: 99%